1987
DOI: 10.1016/0025-5408(87)90032-8
|View full text |Cite
|
Sign up to set email alerts
|

A search for luminescence of the trivalent manganese ion in solid aluminates

Abstract: As an alternative way of examining the prospects of the trivalent manganese ion as a luminescent centre in glasses, AI203:Mn , ZnAI204:Mn and LaAIO3:Mn were investigated by means of spectrofluorometry. The luminescent species identified were divalent and tetravalent manganese and impurities (chromium), whereas trivalent manganese did not show luminescence at wavelengths ~ 800 nm in LaAIO3:Mn and ZnAI204:Mn and i000 nm in AI203:Mn for T down to liquid helium temperature. It is argued that both a strong crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 8 publications
3
10
0
1
Order By: Relevance
“…Since a small amount of Mn 2+ ions can be always present in the prepared ZnAl 2 O 4 as an impurity, it is possible that the observed broad emission around 500 nm has some contribution from Mn 2+ ions. A similar PL emission around 520 nm has been observed earlier in ZnAl 2 O 4 nano-phosphors, wherein it was attributed to defectmediated host lattice emission (Van Die et al 1987;Xiao-Jun Wang et al 2003). The PL emission at 500 nm has been also reported due to Mn 2+ by Singh et al (2008), which corresponds to 4 T 1 -6 A 1 transition of Mn 2+ ions.…”
Section: Structural Characterizationsupporting
confidence: 81%
“…Since a small amount of Mn 2+ ions can be always present in the prepared ZnAl 2 O 4 as an impurity, it is possible that the observed broad emission around 500 nm has some contribution from Mn 2+ ions. A similar PL emission around 520 nm has been observed earlier in ZnAl 2 O 4 nano-phosphors, wherein it was attributed to defectmediated host lattice emission (Van Die et al 1987;Xiao-Jun Wang et al 2003). The PL emission at 500 nm has been also reported due to Mn 2+ by Singh et al (2008), which corresponds to 4 T 1 -6 A 1 transition of Mn 2+ ions.…”
Section: Structural Characterizationsupporting
confidence: 81%
“…The very strong band at 290 nm can be attributed to the superposition of the 4 A 2 -4 T 1 transition of Mn 4ϩ ions and a charge transfer band. 5,9,11,13 Electron paramagnetic resonance ͑EPR͒ spectra of Mn:YAlO 3 powder samples were recorded with an X-band EMX Bruker spectrometer at room temperature. In such a setup, two types of paramagnetic centers, Mn 2ϩ ions, Sϭ 5 2 , and Mn 4ϩ ions, Sϭ 3 2 can be registered.…”
mentioning
confidence: 99%
“…For this same transition and E/D = 0.00, a resonance line close to 6.0 and a second close to 2.00 may appear. The EPR measurements show that the studied vesuvianite crystals differ in the types of electron defects and in the crystal sites occupied by Fe 3+ (Castner et al 1960;Pan and Nilges 2014;SivaRamaiah et al 2011;van Die et al 1987). It is concluded that, in the pink vesuvianite, Fe 3+ is present in two sites, a tetrahedral site when Fe 3+ → Si 4+ and a second with low symmetry when Fe 3+ substitutes for Al 3+ in Y sites.…”
Section: Epr Spectramentioning
confidence: 91%